Sites of Japan's Meiji industrial revolution iron and steel, shipbuilding and coal mining, Japan: summary of nomination to the World Heritage list - Kato, Koko 1959-; Government of Japan Department of Industrial Heritage September 17, 2013$e ([Tokyo] Department of Industrial Heritage, Cabinet Secretariat, Government of Japan World Heritage Council for the "Sites of Japan's Meiji Industrial Revolution" National Congress of Industrial Heritage, 2013)
This series of industrial heritage sites demonstrates the history of Japan's Meiji Industrial Revolution, which laid the foundation of the Nation of Industry today.

The nomination that includes such large-scale industrial sites, the working sites under private management, is a unique case globally. It presents a new model for the conservation of cultural properties that satisfies international expectation. --[Book back cover]
Title from cover.
Written in two (2) diffetent language (English and Japanese)
Keywords: Industrial revolution -- Japan; World Heritage areas -- Japan; Shipbuilding industry -- Japan -- History; Iron industry and trade -- 19th-20th century -- History -- Japan; Steel industry and trade -- History -- Japan -- Meiji period; Coal mines and mining -- History -- Japan; Japan